Severe hypoproteinemia as a harbinger of Ménétrier's disease in autoimmune pancreatitis - Chebli,Julio Maria Fonseca (2017)
Summary Ménétrier's disease is an extremely rare disease of unknown etiology causing gastric mucosal hypertrophy and protein-losing gastropathy. Rare cases of this condition have been reported in patients with autoimmune diseases. However, to the best of our knowledge, Ménétrier's disease associated with autoimmune pancreatitis (AIP) has never been reported. We described a case of severe hypoproteinemia as a harbinger of Ménétrier's disease associated with AIP. The patient was successfully treated with octreotide and high-protein diet, which led to symptomatic remission and significant improvement in serum levels of albumin and recovery of the nutritional status. Thus, in AIP patients presenting with severe and persistent hypoproteinemia without apparent cause, clinicians need to consider Ménétrier's disease in the differential diagnosis. In this setting, endoscopic evaluation with histological examination of gastric biopsy material, including a full-thickness mucosal biopsy of involved mucosa, may be helpful in promptly establishing the diagnosis and allowing appropriate and timely therapy.